(untitled) (Media Kesehatan Masyarakat Indonesia, 2018)
Autism is a brain disorder of pervasive development in children characterized by disturbances and delays in the fields of cognitive, imagination, language, behavior, communication, and social interaction. Based on data from the Indonesian Autism Foundation in 2013, there are 250 thousand people in Palangka Raya City, 20% of them or around 50,000 are children and an estimated 100 children of autism. E-Therapy Autism Child with Multimedia Approach (EAMA) is an e-therapy created by researchers, which includes elements of e-learning. EAMA is a multimedia application software, a combination and development of autistic therapy method of Applied Behavioral Analysis (ABA) and Treatment and education of autistic and Handicapped Children Related Communication (TEACCH). EAMA’s target target is children with autism to improve optimally cognitive, psychomotor and affective in children with autism. EAMA facilitates interventions for behavior change, and enhances psychomotor abilities. In children with autism they are easier to receive information through audio visual. EAMA is a multimedia that can help parents at home while with autism children as an exercise, and also as a learning method for autism teachers in school while teaching. After EAMA then accompanied by practice or simulation on this part as an evaluation of the increase in the ability of autism children. This research was conducted at Sekolah Khusus Melati Ceria (SKMC), Palangka Raya City, 30 people as samples, with total sampling. Experimental design with one group pre and post test, which measures the level of psychomotor and affective abilities of autism children, before and with an intervention with the application designed by the researcher, namely EAMA. Statistical analysis test with Wilcoxon. Research Results: Psychomotor level, before and after given the EAMA method ρ (0,000) <0,05 and Z (-4,899), then there is the influence of EAMA method with psychomotor level before and after giving EAMA method. At the affective level, the value of ρ (0,000) <0,05 with a value of Z (Z -5,292, there is an effect of giving EAMA methods with an increase in affective value in children with autism.